(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

Expand (1-6x)^4 (1+2x)^7 in ascending powers of x up to and including the terms in x^3

2. Relevant equations

(1-6x)^4 (1+2x)^7

3. The attempt at a solution

Firstly, I expand (1-6x)^4

= (1)^4 + 4C1 (-6x) + 4C2 (-6x)^2 + 4C3 (-6x)^3 + ...

= 1 + 4(-6) + 6 (36x^2) + 4(-216^3) + ...

= 1 -24x + 216^2 - 864x^3 + ...

Then after that, I expand (1+2x)^7

= (1)^7 + 7C1 (2x) + 7C2 (2x)^2 + 7C3 (2x)^3 +...

= 1 + 7 (2x) + 21 (4x^2) + 35 (8x^3) + ...

= 1 + 14x + 84x^2 + 280x^3 + ...

Finally, I expand (1-6x)^4 (1+2x)^7 together...

= (1-24x+216x^2=864x^3+...) (1+14x+84x^2+280x^3+...)

= 1+14x+84x^2+280x^3-24x-336x^2-2016x^3+3024x^3-864x^3+...

= 1 -10x-252x^2+2240x^3+...

My final answer is wrong. It should be 1-10x-36x^2+424x^3+...

Can someone help me solve this? Thanks.:tongue:

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Binomial Expansion

**Physics Forums | Science Articles, Homework Help, Discussion**